The role of health mediation in investigation of Hantavirus cases among informal settlements inhabitants of Cayenne area, French Guiana, 2022–2023 - Oberlis, Margot; Guyot, Marion; Le Turnier, Paul; Carvalho, Luisiane; Succo, Tiphanie; Rousset, Dominique; De Thoisy, Benoit; Gaillet, Mélanie; Lavergne, Anne; Vandentorren, Stéphanie; Epelboin, Loïc (Frontiers in Public Health, 2024)
Context In 2022, four severe cases of hantavirus pulmonary syndrome (HPS) were reported in patients from informal settlements around Cayenne, the main city in French Guiana. Regional Health Agency (RHA) was commissioned by the French Public Health Agency to estimate the seroprevalence of hantavirus infections in the neighborhoods of confirmed cases of HPS. RHA then commissioned the French Red Cross (FRC) mobile public health team, providing support in environmental health issues to the population living in informal settlements by health mediators, to facilitate the investigation. The objective of this study was to describe the health mediators' activities and to evaluate their impact on the efficiency of the investigation. Method The health mediators’ team was specifically trained by virologist and infectiologist specialized in SPHHPS. They helped the investigating team and health workers at various steps of the investigation. These interventions are then described in the results section. Results The investigation took place between Nov. 2022 and March 2023 in three neighborhoods. During the pre-investigation activities, the mediators raised awareness about HPS of 343 people, among whom 319 (93%) planned to participate in the investigation. Altogether, 274 people finally participated in the investigation, including, i.e. 30.8% of the estimated population living in the three concerned settlements. The global proportion of patients with positive IgG anti-hantavirus was 5.1%. The health mediators team supported the following steps: preliminary meetings and training modules, identification of resource persons, field visits and awareness and information campaigns (pre-investigation); on field data collection in informal settlements (per-investigation) and communication of individual results, public feedback meeting (post-investigation). Discussion/Conclusion The involvement of mediators was probably a factor in the success of the public health response to socially vulnerable people living in the investigated neighborhoods. The preliminary prevention activities helped to raise awareness of the health risk and to enroll participants. Health mediation and outreach activities seem relevant tools of epidemiological field investigations in diseases affecting inhabitants of informal settlements.